Confocal Laser Scanning Microscopic Evaluation of Sealer Penetration in Root Canals of Teeth with the butterfly and Non-butterfly Effect: An In vitro Study - Sathish, Abraham; Ramesh, Karad Rohini; Ruchika, N. Jain; Sneha, D. Vaswani; Harshal, B. Najan; Rashi, R. Lalwani (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The study aimed to investigate the penetration depth of calcium hydroxide-based root canal sealer into buccolingual and mesiodistal aspects of roots with and without the butterfly effect at coronal and middle root sections. METHODS AND MATERIALS: Twenty single-rooted maxillary premolars were decoronated at the cementoenamel junction and viewed under a light microscope and grouped as Group 1 – butterfly (B) and Group 2 – non-butterfly according to the presence or absence of the effect. Canals were prepared till working length followed with copious irrigation. Canals were finally rinsed with 5 ml of 17% ethylenediaminetetraacetic acid solution and activated using EndoActivator followed by obturation using gutta-percha (warm vertical compaction technique) with Sealapex sealer. To provide fluorescence for confocal laser scanning microscopy (CLSM), the Sealapex was mixed with rhodamine B dye. Root sectioning yielded coronal and middle sections. CLSM was used to assess the penetration of the sealer. STATISTICAL ANALYSIS: Shapiro–Wilk test, unpaired “t-test.” RESULTS: Teeth with the butterfly effect had greater mean penetration buccolingually (905.2 μm) than mesiodistally (182.1 μm; p < 0.001). Coronal sections had greater penetration (517.4 μm) compared with the middle (354.6 μm). CONCLUSION: Sealapex sealer exhibited maximum tubular penetration in teeth with butterfly effect in buccolingual direction at the coronal third level.